The alderfly genus Indosialis Lestage, 1927 (Megaloptera: Sialidae) in Thailand and Laos, with a description of a new species - Piraonapicha, Kanyakorn; Sangpradub, Narumon; Jaitrong, Weeyawat; Liu, Xingyue (Zootaxa, 2020)
Indosialis Lestage, 1927 is a small and rare megalopteran genus belonging to the family Sialidae and endemic to the Oriental region. The Thai and Lao species of Indosialis are herein revised by an integrative approach combining morphological and molecular evidence, including two species: Indosialis bannaensis Liu, Yang & Hayashi, 2006 and Indosialis siamensis sp. nov. The pupal stage of Indosialis is reported here for the first time. Indosialis siamensis sp. nov. can be distinguished from its congeners by 1) the brown head and prothorax (orange in congeners); 2) the apical tooth of right mandible in male sharply angulated (truncate or almost absent in congeners); and 3) the distinct sac-like structure present in male genitalia (indistinct or absent in congeners). The new species coexists with I. bannaensis in Loei Province, northeastern Thailand. Both species inhabit slow-flowing or sluggish streams that are usually covered by Colocasia esculenta (L.) Schott (Araceae).